"Secrets" of Norwegian cross-country skiers - Myakinchenko, E. B.; Kryuchkov, A. S.; Volkov, M. V.; Khramov, N. A. (Theory and Practice of Physical Culture, 2017)
Abstract: The article reports and analyses opinions of the leading Norwegian experts, coaches and athletes (at an international workshop the Norwegian Ski Federation held in Trondheim) on the key elements of the modern Norwegian cross-country skiers` training system - that may explain their domination in the global ski racing sport. The reports included the reports by H.-C. Holmberg (Sweden), M. Bjørgen, E. Kristiansen, A. Sandbakk; M. Braten, P. Northug (Norway); analyse the interviews of Tor Arne Hetland (senior coach of the men`s national ski racing team of Norway and personal coach of Martin Sundby) and A. Sandbakk, research division head at the Olympiatopen (Norwegian Olympic Team Training and Analytical Centre); and analyse the data mined from different sources by the Analytical Department of the national FSBA (Federal State Budget-supported Agency) Sport Training Centre on the modern training systems applied by Norwegian cross-country skiers.Special attention is given to description of the modern strength training components that are actually considered a basis for the cross-country skiers` technical training cycles and widely applied to increase the power and efficiency of the propulsive movement phases in the ski stride. The article also considers the high-intensity competitive training modes widely applied by the Norwegians to attain the highest effectiveness of the "competitive functionality system".